PENGARUH BIRTH BALL TERHADAP KALA I FASE AKTIF PADA IBU BERSALIN DI PMB “Y” DI KARAWANG TAHUN 2022 - Rina Dwi Anggraeni; Euis Atikah (Journal of Innovation Research and Knowledge, 2023)
Labor is the birth of a baby, placenta, and amniotic membranes from the uterus to the outside world. The cause of complications in childbirth that causes increased mortality and morbidity in the mother and fetus is prolonged labor. The high number of old events during the active phase I in West Java. This research aims to know the direct and indirect influence as well as the Birth ball exercise towards the first stage of the active phase in PMB “Y” In Karawang year 2022. With the method of quantitative approaches that use design cross-sectional. The population in this study were all labour women in PMB “Y” in karawang. The sample in this study were 15 respondents with purposive sampling technique. This research instrument uses partographs and observation sheets to assess the length of the first stage of the active phase. The method of analysis by SEM analysis using Smart-PLS 4. The results of the hypothesis testing above show that H1 is accepted, namely there is a significant influence of Birth Ball on the active phase of Kala I with a path coefficient of 0.780 and a P-Value of 0.000 <0.05. Each Birth Ball intervention will affect the active phase of Kala I. In the 95% confidence interval, the influence of Birth Ball on the active phase of Kala I lies between 50.3% and 95.7%. Birth Ball in influencing the active phase of Kala I has a high influence at the structural level (F Square = 1.554). The need to convey information about Birth Ball is one of the efforts to deal with problems that often occur in the active phase of Kala I. Carrying out Birth Ball is considered very important. When the mother does the Birth Ball series properly, the influence on the active phase of Kala I will increase to 95.7%.